Bibliography of the Athabasca river basin: a digital tool for knowledge building and open access - Elliott, Colin (ABC Copyright Forum, 2010)
https://prezi.com/secure/1fe2e2d00d9e32637e0674071f78ad39e770e0a3/ Athabasca University’s Athabasca River Basin Research Institute is developing a bibliography of the Athabasca River Basin (BARB) as a digital tool to promote knowledge building and information sharing. This highly utilitarian, multidisciplinary bibliographic database has science, social science, humanities, business/commerce, and First Nations components. The BARB will support open access and serve as a foundation for Athabasca River Basin research as well as other scholarly activities. The presentation will demonstrate the functionality and operation of the BARB and discuss the opportunities and challenges for using a database to facilitate the sharing of knowledge, research, and scholarly communication through open access.